Peran Halal Lifestyle, Digital Experience, dan Store Atmosphere terhadap Loyalitas Konsumen: Kajian Literatur dalam Perspektif Ekonomi Syariah - Laura Aurellia Fayza Kusumaputri; Moh. Mukhsin (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2026)
This study aims to analyze the significance of the halal lifestyle, digital experience, and store atmosphere in fostering consumer loyalty, utilizing a literature review method. A qualitative approach was adopted, drawing upon scholarly journals, academic books, and prior research relevant to the topic. Data collection was conducted through documentation and a systematic literature search. Content analysis was employed to identify themes, patterns, and relationships among concepts related to consumer loyalty within the framework of the Islamic economy. The findings indicate that the halal lifestyle serves as a core value that instills trust and a sense of comfort in consumers. Digital experiences facilitate access to information, interaction, and services, thereby enhancing consumer engagement with the brand. Meanwhile, the store atmosphere generates an emotional experience that supports satisfaction and encourages repeat visits. These three elements are interconnected in creating a meaningful consumption experience and play a pivotal role in boosting consumer loyalty. This study offers a conceptual understanding of how the integration of halal values, digital experiences, and the physical environment shapes consumer loyalty from the perspective of the Islamic economy.